(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The objective of the study is to analyze the economic impact of Covid-19 on travel and tourism agencies in the city of Chachapoyas in Peru during the year 2021. The methodology is developed under a quantitative approach, gathering information through interviews and surveys applied to 31 travel and tourism agencies in the city of Chachapoyas. In the results, it has been determined that the sanitary measures given by the government because of the Covid-19 pandemic, causing a serious negative economic impact on travel and tourism agencies, resulting in 29% of the total number of tourist agencies closing temporarily, 19.4% of companies are operating part-time, which means that almost half of the travel and tourism agencies have decided to reinvent themselves in other commercial areas, due to the low demand of domestic and foreign tourists who visit us. It is concluded that the impacts of the pandemic on these sectors require adjustments in the decision making process.